2022
DOI: 10.1111/den.14266
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term transmural drainage of pancreatic fluid collections with double pigtail stents following lumen‐apposing metal stent placement improves recurrence‐free survival in disconnected pancreatic duct syndrome

Abstract: Objectives Disconnected pancreatic duct syndrome (DPDS) is the most common cause of pancreatic fluid collection (PFC) recurrence. While long‐term transmural drainage with plastic stents is the preferred endoscopic approach, there is a paucity of literature on patients undergoing initial drainage with lumen‐apposing metal stents (LAMS). We describe our experience managing patients with DPDS. Methods A retrospective review of a prospectively maintained database (November 2015–September 2020) was performed lookin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 20 publications
0
35
0
Order By: Relevance
“…In Pawa et al .’s study, 6 DPS replacement after LAMS removal was successful in only 44% (21/48) of the patients with DPDS, much lower than the 75% reported previously 4 . To explain this low success rate, they explored factors associated with failed DPS replacement and identified a longer duration of LAMS placement as a factor 6 . Notably, in their study, the median duration of LAMS placement was 28 days in the successful DPS replacement group and 53 days in the unsuccessful DPS replacement group 6 .…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…In Pawa et al .’s study, 6 DPS replacement after LAMS removal was successful in only 44% (21/48) of the patients with DPDS, much lower than the 75% reported previously 4 . To explain this low success rate, they explored factors associated with failed DPS replacement and identified a longer duration of LAMS placement as a factor 6 . Notably, in their study, the median duration of LAMS placement was 28 days in the successful DPS replacement group and 53 days in the unsuccessful DPS replacement group 6 .…”
mentioning
confidence: 95%
“…indicate that long‐term DPS placement in situ can prevent PFC recurrence; however, these studies provide no answers about when to remove the DPS after long‐term placement. Further, it is unclear whether long‐term indwelling DPS helps reduce the incidence of new‐onset DM, and whether there was a difference in new‐onset DM between the two groups in Pawa et al .’s study (i.e., with and without DPS) is a matter of considerable interest 6 . Regarding the safety of leaving a DPS in place for a long period, a recent report has stated that, during a median follow‐up of 21 months, colonic perforations occurred in 8.3% (3/36) of the PFC patients with long‐term DPS placement 10 .…”
mentioning
confidence: 99%
“…In our study, metal stents were replaced with plastic stents after resolution of walled-off necrosis (WON). The clinical settings were different from those described in previous studies where index drainage was performed using plastic stents 2 3 . We believe that this is a highly relevant scenario in the current era where large-caliber metal stents (LCMSs) are being increasingly utilized for the management of WON.…”
mentioning
confidence: 99%
“…We read with interest the randomized controlled trial by Chavan et al demonstrating that in patients with walled-off necrosis (WON) and disconnected pancreatic duct (DPD), deployment of plastic stents after removal of a large-caliber metal stent (LCMS) did not reduce the recurrence of pancreatic fluid collections (PFCs) 1 . In patients with resolved WON and DPD, the current practice is to leave plastic stents indefinitely to maintain the patency of the cystenterostomy tract, as published retrospective studies have shown that this strategy reduces the risk of recurrent PFCs 2 3 4 5 . What is the explanation for the discordant results of the Chavan et al trial?…”
mentioning
confidence: 99%